Electrospinning of highly aligned and covalently cross‐linked hydrogel microfibers. Issue 22 (26th June 2014) - Bassil, Maria; AL Moussawel, Judy; Ibrahim, Michael; Azzi, Georges; El Tahchi, Mario
ABSTRACT Smart polyelectrolyte hydrogels are increasingly studied toward the realization of soft microactuators. This study focuses on the fabrication of highly aligned and covalently cross‐linked polyacrylamide hydrogel microfibers by electrospinning technique following two‐stage polymerization. The engineering of the reaction timescale of the precursor, such that the material gels shortly after spinning, is described and the design of the electrospinning setup, to generate highly aligned fibers, is presented. In addition the effect of the operating parameters on the fibers average diameter is investigated. The generated fibers are 15 cm long with average diameter ranging between 100 nm and 1.10 μm. The fibers diameter is controlled by adjusting the thickener type and concentration in the precursor and the electrospinning processing parameters. Thinner fibers are generated at lower thickener molecular weights and concentrations as well at lower flow rate and higher voltage. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 41092.